2012
DOI: 10.1097/gme.0b013e318254102b
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid levels in women with premature ovarian failure

Abstract: Higher TC and LDL levels in women with POF compared with the control group suggest that estrogen deprivation in women with POF leads to unfavorable lipid changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 16 publications
4
26
1
2
Order By: Relevance
“…Earlier studies have described several changes in lipids among women with POI, as early as in their 30s, similar to the present findings in climacteric women at the age of 46: higher TC (29,35), higher HDL-C (29), higher LDL-C (35) and higher triglycerides (27). There is little research on the lipid profile of women with POI in their 50s, but Daan et al (28) found no difference in TC, LDL-C or triglyceride levels between women with POI and age-matched premenopausal controls, whereas they found HDL-C levels were higher in women with POI.…”
Section: Discussionsupporting
confidence: 92%
“…Earlier studies have described several changes in lipids among women with POI, as early as in their 30s, similar to the present findings in climacteric women at the age of 46: higher TC (29,35), higher HDL-C (29), higher LDL-C (35) and higher triglycerides (27). There is little research on the lipid profile of women with POI in their 50s, but Daan et al (28) found no difference in TC, LDL-C or triglyceride levels between women with POI and age-matched premenopausal controls, whereas they found HDL-C levels were higher in women with POI.…”
Section: Discussionsupporting
confidence: 92%
“…11 A proinflammatory change in cytokine activity has been observed after menopausal transition 28 that can produce an unfavorable change in the vascular system, through endothelial dysfunction and change in aortic wall composition. 29 Estrogen deprivation is also associated with adverse changes in metabolic profile after menopause, through an increase in body weight and an atherogenic lipid profile, 30 and both of these alterations were observed in our experimental animals.…”
Section: Discussionmentioning
confidence: 82%
“…1,12 ; however, a recent study of women with ovarian failure and low estradiol concentrations also reported high total cholesterol and low-density lipoprotein cholesterol concentrations. 13 In the present study using percentiles of sex hormones generated in 10-year age groups and thus circumventing the age-dependent changes in sex hormones, we observed that low plasma concentrations of endogenous estradiol were associated with modest adverse effects on cardiovascular risk factors, and that high plasma concentrations of endogenous testosterone were associated with adverse effects on plasma total cholesterol, body mass index, plasma glucose, and blood pressure in women. This suggests that low estradiol is directly associated with cardiovascular risk, whereas the risk observed for high testosterone may be mediated through other cardiovascular risk factors.…”
Section: Arterioscler Thromb Vasc Biolmentioning
confidence: 82%